Molecular Detection of Feline Coronavirus in Captive Non-Domestic Felids from Zoological Facilities - Gabriele Ratti; Angelica Stranieri; Alessia Giordano; Maurizio Oltolina; Eleonora Bonacina; William Magnone; Manuel Morici; Giuliano Ravasio; Saverio Paltrinieri; Stefania Lauzi (Animals, 2022)
Cases of feline infectious peritonitis (FIP), a disease with a high mortality rate caused by the feline coronavirus (FCoV), have been reported in non-domestic felids, highlighting the need for surveys of FCoV in these endangered species. With the aim of adding information on FCoV prevalence in captive non-domestic felids, samples (feces or rectal swabs and, when available, oral swabs, blood, and abdominal effusion) collected between 2019 and 2021 from 38 non-domestic felids from three different zoological facilities of Northern Italy were tested for evidence of FCoV infection via RT-qPCR. Three animals were found to be FCoV positive, showing an overall 7.9% FCoV prevalence ranging from 0% to 60%, according to the zoological facility. FCoV infection was detected in tiger cubs of the same litter, and all of them showed FCoV-positive oral swabs, with low viral loads, whereas in one animal, FCoV presence was also detected in rectal swabs at low FCoV copy numbers. Future studies should be carried out, including samplings from a higher number of captive non-domestic felids, in order to gain a deeper knowledge of FCoV epidemiology within these populations.